2010
DOI: 10.1164/rccm.200908-1189oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension and Computed Tomography Measurement of Small Pulmonary Vessels in Severe Emphysema

Abstract: Rationale: Vascular alteration of small pulmonary vessels is one of the characteristic features of pulmonary hypertension in chronic obstructive pulmonary disease. The in vivo relationship between pulmonary hypertension and morphological alteration of the small pulmonary vessels has not been assessed in patients with severe emphysema. Objectives: We evaluated the correlation of total cross-sectional area of small pulmonary vessels (CSA) assessed on computed tomography (CT) scans with the degree of pulmonary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(168 citation statements)
references
References 43 publications
6
161
0
1
Order By: Relevance
“…The area under the curve for the PA:A ratio was 0.83 (95% CI, 0.72-0.93; ible, requires minimal training, and performs better than echocardiography for the identifi cation of PH in patients with severe COPD. 11,16,26,27 Estimates of the prevalence of PH in COPD vary widely from as low as 10% to as high as 85% depending on the severity of the underlying lung disease and the diagnostic criteria as well as approach used. 11,[28][29][30] Accurate estimates have also been problematic, because RHC is not routinely used in patients with COPD, particularly in those with moderate disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area under the curve for the PA:A ratio was 0.83 (95% CI, 0.72-0.93; ible, requires minimal training, and performs better than echocardiography for the identifi cation of PH in patients with severe COPD. 11,16,26,27 Estimates of the prevalence of PH in COPD vary widely from as low as 10% to as high as 85% depending on the severity of the underlying lung disease and the diagnostic criteria as well as approach used. 11,[28][29][30] Accurate estimates have also been problematic, because RHC is not routinely used in patients with COPD, particularly in those with moderate disease.…”
Section: Resultsmentioning
confidence: 99%
“…However, most of these studies were conducted in heterogeneous populations with various underlying lung diseases, thus, limiting their application to patients with COPD. [14][15][16][17][18][19][20] We showed that CT image-measured relative PA enlargement, defined as a PA:A ratio . 1, identifies patients at increased risk of COPD exacerbation and hospitalization 21 ; however, the mechanism underlying relative PA enlargement has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuoka reported that the %CSA<5 was found to have a negative correlation with the extent of emphysema, degree of airflow limitation, and severity of pulmonary hypertension [15][16][17] . Further, Karayama reported that the %CSA<5 significantly decreased after chemotherapy and mentioned that this result was indicative of the potential vascular toxicity induced by chemotherapy 18) .…”
Section: Discussionmentioning
confidence: 99%
“…CT measurements of pulmonary CSA have been described in previous literature 17,18) . In brief, the following procedures were performed.…”
Section: Ct Measurement Of Pulmonary Small Vesselsmentioning
confidence: 99%